The Analysis of Factors Constructing Employee Productivity in The Operational Field in PT. Sumber Alfaria Trijaya Branch Lombok - Kusumanegara, Indah Suprabawati (International Research Journal of Management, IT & Social Sciences, 2018)
This study was conducted to analyze the factors that shape the field of operational productivity of employees at PT. Source Alfaria Trijaya Branch Lombok. The method used in this research is method survey with a sample of 85 respondents were determined by simple random sampling. The analytical tool used is a factor analysis. Based on the analysis that has been done, it can be concluded, there are three factors that shape the field of operational productivity of employees at PT. Source Alfaria Trijaya Branch Lombok, first factor is formed from factors Education and Training (Training), Work Discipline, Work Experience, Job Satisfaction, Morale, Morale, Work Environment and Kompensasi. Factor both shaped by factors Leadership, Education Level, Job Skills, Job Stress and Organizational Culture. The third factor is formed by motivational factors. The first factor has a value which means that the largest percentage of variance of these factors have a relationship that is the most powerful or the most dominant in shaping the field of operational productivity of employees at PT. Source Alfaria Trijaya Branch Lombok.